Teaching strategies for library instruction: directions from the literature - Nove E Variant Anna,; Kaur, Kiran; Yanti Idaya A.M.K., (Malaysian Journal of Library and Information Science, 2023)
This paper proposes teaching strategies and techniques for library instruction in academic libraries to achieve the intended goals. The recommendations are based on insights from previous research in library instruction with the intention to identify possible strategies and techniques for different user groups. This study applied a systematic literature review method, using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol to examine the use of teaching strategies and techniques in library instruction programs. The Web of Science (WoS) and Scopus databases were searched for relevant literature using specific keywords. Applying the inclusion criteria, a total of 27 articles out of the 1380 documents extracted, were deemed relevant to the study. The results show that library instruction is usually conducted in the form of individual sessions. Teaching strategies used by librarians include flipped classroom, faux flip, classroom teaching, research clinic, consultation, asynchronous learning, and online synchronous learning, among others. These teaching strategies improved engagement and relationships between students and librarians, while impacting critical thinking, confidence and self-directed learning. It is concluded that librarians should consider adopting and combining teaching strategies based on individual needs and use technology to improve teaching effectiveness and increase student learning. This study shows that most studies on library instruction have only partially addressed instructional strategies. A critical review of the literature revealed that a strategic shift in the management of library instruction is necessary to achieve the intended outcomes. In this study, three teaching strategies for library education are proposed, namely Embracing for freshman, Encouraging for sophomore, and Leveraging for postgraduates.